2017
DOI: 10.1002/cpbi.33
|View full text |Cite
|
Sign up to set email alerts
|

Data Analysis Pipeline for RNA‐seq Experiments: From Differential Expression to Cryptic Splicing

Abstract: RNA sequencing (RNA-seq) is a high-throughput technology that provides unique insights into the transcriptome. It has a wide variety of applications in quantifying genes/isoforms and in detecting non-coding RNA, alternative splicing, and splice junctions. It is extremely important to comprehend the entire transcriptome for a thorough understanding of the cellular system. Several RNA-seq analysis pipelines have been proposed to date. However, no single analysis pipeline can capture dynamics of the entire transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 40 publications
(35 reference statements)
2
29
0
Order By: Relevance
“…Gene level counts were obtained as the sum of total reads mapped to respective genes. As expected, based on principal component analysis using gene counts (Yalamanchili et al, 2017)., sample clustering reflected genotype and age ( Figure S7).…”
Section: Drosophila Rna Sequencingsupporting
confidence: 75%
“…Gene level counts were obtained as the sum of total reads mapped to respective genes. As expected, based on principal component analysis using gene counts (Yalamanchili et al, 2017)., sample clustering reflected genotype and age ( Figure S7).…”
Section: Drosophila Rna Sequencingsupporting
confidence: 75%
“…DEIs were computed using the pipeline described in ( Yalamanchili et al, 2017 ). Isoform expression was quantified from raw pair-end fastq files (RNA-Seq data) using Kallisto ( Bray et al, 2016 ), an alignment free transcript quantification program.…”
Section: Methodsmentioning
confidence: 99%
“…We sequenced four samples from both the control and NUDT21 knockdown conditions, but excluded one control sample with <10 million reads, and one knockdown sample with unusually low NUDT21 levels (<2% of other knockdown samples). We then performed principle component analysis (PCA) on gene counts as previously described and confirmed that the treatment groups clustered ( Figure 4—figure supplement 1A ) (Yalamanchili et al, 2017).…”
Section: Methodsmentioning
confidence: 53%
“…We performed a PCA as previously described to confirm that the treatment groups separated ( Figure 4—figure supplement 1B ) (Yalamanchili et al, 2017). We then computed protein level changes as log 2 fold change values and plotted them against their relative mRNA length change ( Figure 4E ).…”
Section: Methodsmentioning
confidence: 99%